An Investigation into Syntactic and Semantic Features of English and Vietnamese Proverbs Expressed in Relational Identifying Processes - Nguyễn Thị Thúy Hoa (2012)
Proverbs are the part of the oral tradition of a cultural group. Because they are usually spoken and not written, they must be vivid and have the quality that they can be easily remembered. If the ….